KEADILAN HUKUM DALAM PENERAPAN DISKRESI KEPOLISIAN GUNA PENGHENTIAN PENYIDIKAN TINDAK PIDANA KECELAKAAN LALU LINTAS PERSPEKTIF UNDANG – UNDANG NOMOR 2 TAHUN 2002 - Ciptono (Lex Journal: Kajian Hukum & Keadilan, 2022)
ABSTRACT This study aims to examine legal justice in the application of police discretion to stop the investigation of criminal acts of traffic accidents at this time, the problems and solutions of legal justice in the application of police discretion to stop the investigation of traffic accidents from the perspective of Law No. 2 of 2002. This approach method uses sociological juridical approach with qualitative methods supported by primary and secondary data. With the research specification is descriptive analytical, so that the deepening of the problem is very necessary. The results of this study concluded that: 1) In practice, Article 18 of Law Number 2 of 2002 concerning the Indonesian National Police which is the basis for police discretionary actions has not been used as a legal umbrella, although in practice many investigators have done so. 2) From the aspect of legal substance, in practice, discretion is applied to the field of traffic or other matters that have not touched the task of investigating and investigating criminal acts. From the structural aspect, it can be seen in the administrative practice of internal police investigations that have not accommodated, stopping criminal investigations on the legal basis of police discretion. Meanwhile, from the cultural aspect, the Police leadership has paid attention to the rise of traffic accidents with the category of minor and moderate accidents where the perpetrator and the reporter have peace and forgiveness and compensation is available to stop, but it has not become a legal product that can be used as a legal umbrella. national. Keywords: Justice, Discretion, Termination, Investigation